Mifepristone modulates serotonin transporter function - Li, Chaokun; Shan, Linlin; Jiang, Hongbo; Li, Xinjuan; Wei, Linyu; Li, Dongliang (Neural regeneration research, 2014)
Regulating serotonin expression can be used to treat psychotic depression. Mifepristone, a glu- cocorticoid receptor antagonist, is an effective candidate for psychotic depression treatment. However, the underlying mechanism related to serotonin transporter expression is poorly un- derstood. In this study, we cloned the human brain serotonin transporter into Xenopus oocytes, to establish an in vitro expression system. Two-electrode voltage clamp recordings were used to detect serotonin transporter activity. Our results show that mifepristone attenuates serotonin transporter activity by directly inhibiting the serotonin transporter, and suggests that the se- rotonin transporter is a pharmacological target of mifepristone for the treatment of psychotic depression.